Participação política das mulheres do estado do Tocantins no sistema eleitoral proporcional e a cota de gênero: uma história contada pela memória das protagonistas - Oliveira, Thiago Franco (Universidade Federal do Tocantins, 2022)
This dissertation aimed to investigate and analyze the participation of women in the Brazilian proportional electoral system, especially regarding the reasons for the low number of elected women, the geographic delimitation for the study was the State of Tocantins, and it started from the hypothesis that the population national and that state is composed mostly of women. The objective was to investigate the political underrepresentation of women in the Tocantins legislature from the political trajectory of the elected deputies for the quadrennium 2019 to 2022, as well as to investigate the existence and difficulties in the journey of these women to reach the mandate and to maintain themselves. A qualitative approach was used through oral history, which is at the same time a method of scientific investigation, a source of research, a technique for the production and treatment of recorded testimonies. The methodology allowed, through the interviews, to observe the life history of the interviewees, and later turn them into documents bringing other stories. It was observed that the political rights to vote and to be voted for are listed as fundamental rights of the people, being therefore inherent to human rights, but even with that and with all legal and constitutional advances the political participation of women still proved to be very shy, especially in proportional elections, resulting in low parliamentary representation. It was concluded that all the parliamentarians interviewed were knowledgeable about the quota policies in the electoral system, also pointing out concern with the low number of women in the spaces of power. Finally, it was concluded that the political environment is still not favorable to the entry of other women, being predominantly occupied by men, but it is not impossible for women to occupy spaces in proportion to the number of inhabitants and voters by gender, showing Quotas are used as one of the necessary tools for this.